Validation of a Thai version of the Hope Scale among patients with acute myocardial infarction - Inyoo, Ampika; Polsook, Rapin (Belitung Raya Foundation, Indonesia, 2021)
Background: Hope is essential for patients with acute myocardial infarction, which is often regarded as an active coping for those with life-threatening diseases. Higher hope consistently is related to better health outcomes. However, the instrument for assessing hope has not been previously tested among Thai patients. Objective: This study aimed to assess the validity and reliability of the Hope Scale among Thai patients with acute myocardial infarction patients. Methods: This was an instrument validation study conducted from March to December 2020. A total of 213 patients with acute myocardial infarction were included and selected using a simple random sampling. The back-translation method was used to translate an English version to a Thai version of the scale. Principal Component Analysis (PCA) and Cronbach’s alpha were used for construct validity and reliability. Results: The findings showed that the Cronbach’s alpha of the Thai version of the Hope Scale was acceptable (.75), and the scale consists of four factors, which explained 63.36 % of the total variance. Communalities in each factor ranged from .45 to .84. Overall, the appearance of the factor structures was reasonable and understandable. Conclusion: The reliability and validity of the Thai version of the Hope Scale were suitable for the measurement of hope in Thai patients. This scale can be used by nurses and others to assess hope in Thai patients with acute myocardial infarction.